HISAB AWAL WAKTU SALAT DALAM KITAB RISALAH FALAK AL-ANWAR - Nur Imani Surur; Ahmad Adib Rofiuddin (Salimiya: Jurnal Studi Ilmu Keagamaan Islam, 2025)
This study explores the method and accuracy of the initial calculation of prayer times in the book Risalah Falak Al-Anwar. This book uses a different algorithm concept. The difference lies in the data on solar declination and the equation of time used are stagnant (eternal). The calculation also does not include corrections to the altitude of the place. While other modern prayer time calculation methods use solar declination data and equation of time which are updated annually. The research method used is a literature study with data analysis from the book Risalah Falak Al-Anwar. This study produced two findings, First, the initial calculation of prayer times in the book Risalah Falak Al Anwar is included in the haqiqi tahqiqi method, because in its calculations it already uses the spherical trigonometry formula. The equation of time data is adopted from the book Nur al-Anwar and the solar declination data is calculated manually using the solar longitude difference formula. Second, the results of the calculation of prayer times in the book Risalah Falak Al Anwar are quite accurate, because the largest difference with the Ephemeris is 1 minute 51 seconds.